#TITLE_ALTERNATIVE# - W. MULYANDARI (NIM 12203046), ANDINI
Naturally fractured reservoir (NFR) has a complex system due to its dual-porosity system, the matrix porosity and fracture porosity. In addition, NFR also has a difference in its compressibility value between the matrix and fracture system. Commonly, the compressibility value in the fracture system is much higher than the one in the matrix system. And for that reason, a new and different material balance equation, rather than the general material balance equation which usually used in single-porosity system reservoir, is needed. The material balance equation for dry gas reservoir in NFR has been derived by Bazed3, along with the solution for the equation using a statistical-approach straight-line. But upon utilizing the equation, also its statistical-approach straight-line method, in dry gas naturally fractured reservoirs still generates a tremendous error value. In this paper, it is proposed a new straight-line method to solve the material balance equation in naturally fractured reservoir which has a dual-porosity and dual-compressibility system that can generate the Initial Gas in Place (IGIP) value, both in the matrix and fracture system, more accurately. This method has been tested on solving seven hypothetic cases with various porosity value in fracture system, thus it can comprehend all the three types of naturally fractured reservoir, which are the naturally fractured reservoir Type A where the matrix has much larger amount of reserve compared to the fracture system; naturally fractured reservoir Type B which has an equal amount of reserves, both in matrix and fracture system; and naturally fractured reservoir Type C where the fracture system has a much larger amount of reserve compared to the matrix system. Other than that, also done a sensitivity study to test various values of matrix compressibility (Cm) and fracture compressibility (Cf), and how their values affect the IGIP calculation by the proposed method, both in the matrix and fracture system.